Modulation of the Acute Inflammatory Response Induced by the Escherichia coli Lipopolysaccharide through the Interaction of Pentoxifylline and Florfenicol in a Rabbit Model - Victoria Cazanga; Cristina Palma; Tomás Casanova; Daniela Rojas; Karin Barrera; Cristhian Valenzuela; Aracelly Acevedo; Gabriel Ascui-Gac; Tamara Pérez-Jeldres; Rubén Pérez-Fernández (Antibiotics, 2023)
Background: Experimental reports have demonstrated that florfenicol (FFC) exerts potent anti-inflammatory effects, improving survival in a murine endotoxemia model. Considering the anti-inflammatory and immunomodulatory properties of pentoxifylline (PTX) as an adjuvant to enhance the efficacy of antibiotics, the anti-inflammatory effects of the interaction FFC/PTX over the E. coli Lipopolysaccharide (LPS)-induced acute inflammatory response was evaluated in rabbits. Methods: Twenty-five clinically healthy New Zealand rabbits (3.8 ± 0.2 kg body weight: bw), were distributed into five experimental groups. Group 1 (control): treated with 1 mL/4 kg bw of 0.9% saline solution (SS) intravenously (IV). Group 2 (LPS): treated with an IV dose of 5 µg/kg of LPS. Group 3 (pentoxifylline (PTX) + LPS): treated with an oral dose of 30 mg/kg PTX, followed by an IV dose of 5 µg/kg of LPS 45 min after PTX. Group 4 (Florfenicol (FFC) + LPS): treated with an IM dose of 20 mg/kg of FFC, followed by an IV dose of 5 µg/kg of LPS 45 min after FFC administration. Group 5 (PTX + FFC + LPS): treated with an oral dose of 30 mg/kg of PTX, followed by an IM dose of 20 mg/kg of FFC, and, 45 min after an IV dose of 5 µg/kg of LPS was administered. The anti-inflammatory response was evaluated through changes in plasma levels of interleukins (TNF-α, IL-1β and IL-6), C-reactive protein (CRP), and body temperature. Results: It has been shown that each drug produced a partial inhibition over the LPS-induced increase in TNF-α, IL-1β, and CRP. When both drugs were co-administered, a synergistic inhibitory effect on the IL-1β and CRP plasma concentrations was observed, associated with a synergic antipyretic effect. However, the co-administration of PTX/FFC failed to modify the LPS-induced increase in the TNF-α plasma concentrations. Conclusions: We concluded that the combination of FFC and PTX in our LPS sepsis models demonstrates immunomodulatory effects. An apparent synergistic effect was observed for the IL-1β inhibition, which peaks at three hours and then decreases. At the same time, each drug alone was superior in reducing TNF-α levels, while the combination was inferior. However, the peak of TNF-α in this sepsis model was at 12 h. Therefore, in rabbits plasma IL-1β and TNF-α could be regulated independently, thus, further research is needed to explore the effects of this combination over a more prolonged period.